Reflections on the life and contributions to vegetation science of Lojze Marinček (1932-2023) - Čarni, Andraž; Dakskobler, Igor; Košir, Petra; Marinšek, Aleksander; Šilc, Urban (Hacquetia, 2024)
On April 8, 2023, Lojze Marinček passed away, one of the leading researchers of forest vegetation in the second half of the twentieth century, whose work significantly contributed to knowledge of the forest vegetation of Slovenia.